Prevalence of Medication Errors in a Tertiary Care Teaching Hospital - Manoj Kumar Sethi (Journal of Global Pharma Technology, 2019)
Objective: The purpose of current research is to identify the incidence of all possible prescription errors and to categorise them in a tertiary teaching care hospital of south India. Methodology: This is a prospective observational study conducted for nine months of various departments of (SVS) Medical College and Hospital, Mahabub nagar, Telangana. Suitable data collection forms were designed to meet up the criteria. Patients those agreed to give informed consent were included and those not willing to give consent and of (ICU) were excluded from this study. Patients were monitored on a regular basis from the time of admission to the date of discharge for any type of prescription error and recorded accordingly. Results: Throughout the study duration total 2000 prescriptions were analysed and observed that 400 prescriptions contains some kind of medication errors. More incidences of errors observed in surgery department (34 percent) and least was found in gynaecology department (3.75%). Major types of errors were omission error. Parenteral formulations constitute maximum no. of errors than oral and other external routes.  Conclusion: Most of the errors were omission of dose followed by illegibility, omission of prescriber signature, error in units, omission of route of administration (ROA), over writing, omission of frequency, under prescribing, omission of medication, omission of superscription, irrational prescribing, over prescribing, abbreviations, error in writing ROA, error in dose. Thus the present study threw some light on the need of proper education and training of all health care professional to minimize medication errors by which proper therapeutic goal can be achieved.Keywords: Prescription errors, Omission error, Commission errors, Medication errors.